Epigenetic Modulation Directs Recovery Post LASIK and SMILE Surgery: An Experimental Study - Rohit Shetty; Pooja Khamar; Ramaraj Kannan; Puja Thacker; Nimisha Rajiv Kumar; Arkasubhra Ghosh; Vrushali Deshpande (Life)
Purpose: refractive surgery, such as LASIK and SMILE, induces a wound healing response that leads to significant corneal stromal remodeling. We have shown that the protein profile in the stroma changes dramatically immediately post-surgery. However, the methylation status of the DNA post-refractive surgery remains unknown. Design/Participants: DNA methylation study. Refractive surgery (SMILE/LASIK) performed on donor eye globes. Method: we investigated the epigenetic changes post-surgery in relation to long term ECM remodeling in an experimental ex vivo study design. Donor globes (n = 19) were obtained from the eye bank. Three globes served as non-surgical controls while SMILE (-6DS) and LASIK surgery (-6DS) were performed on eight globes each and incubated for 3 days and 2 weeks (n = 4 per group per time point). Here, we compared the DNA methylation landscapes of LASIK and SMILE stroma using the Illumina Infinium Human Methylation 850 EPIC array (HM850). Results: significant changes in DNA methylation patterns were observed post-operatively in both LASIK and SMILE groups. Specific genes involved in the activation of actin cytoskeleton and inflammation (smad3, prkca and ssh2) showed hypomethylation in LASIK after 2 weeks and LASIK SMILE after 3 days, respectively, suggesting their active role in corneal repair. The genes (gaa, gstm1, mgat1, galnt9 and galnt5) involved in sphingolipid metabolism and mucin biosynthesis showed hypomethylation in SMILE after 3 days. Conclusions: our results suggest that altered DNA methylation patterns may have relevance to the development of complications of haze post-refractive surgery. It also presents the opportunity to utilize drugs that regulate chromatin remodeling for optimal outcomes.